The Horyzons project: a randomized controlled trial of a novel online social therapy to maintain treatment effects from specialist first‐episode psychosis services. Issue 2 (18th May 2021) - Alvarez‐Jimenez, Mario; Koval, Peter; Schmaal, Lianne; Bendall, Sarah; O'Sullivan, Shaunagh; Cagliarini, Daniela; D'Alfonso, Simon; Rice, Simon; Valentine, Lee; Penn, David L.; Miles, Chris; Russon, Penni; et al.
Abstract : This study aimed to determine whether, following two years of specialized support for first‐episode psychosis, the addition of a new digital intervention (Horyzons) to treatment as usual (TAU) for 18 months was more effective than 18 months of TAU alone. We conducted a single‐blind randomized controlled trial. Participants were people with first‐episode psychosis (N=170), aged 16‐27 years, in clinical remission and nearing discharge from a specialized service. They were randomly assigned (1:1) to receive Horyzons plus TAU (N=86) or TAU alone (N=84) between October 2013 and January 2017. Horyzons is a novel, comprehensive digital platform merging: peer‐to‐peer social networking; theory‐driven and evidence‐informed therapeutic interventions targeting social functioning, vocational recovery and relapse prevention; expert clinician and vocational support; and peer support and moderation. TAU involved transfer to primary or tertiary community mental health services. The primary outcome was social functioning at 18 months as measured by the Personal and Social Performance Scale (PSP). Forty‐seven participants (55.5%) in the Horyzons plus TAU group logged on for at least 6 months, and 40 (47.0%) for at least 9 months. Social functioning remained high and stable in both groups from baseline to 18‐month follow‐up, with no evidence of significant between‐group differences (PSP mean difference: –0.29, 95% CI: –4.20 to 3.63, p=0.77). Participants in the Horyzons group had a 5.5 times greater increase in their odds to find employment or enroll in education compared with those in TAU (odds ratio, OR=5.55, 95% CI: 1.09‐28.23, p=0.04), with evidence of a dose‐response effect. Moreover, participants in TAU were twice as likely to visit emergency services compared to those in the Horyzons group (39% vs. 19%; OR=0.31, 95% CI: 0.11‐0.86, p=0.03, number needed to treat, NNT=5). There was a non‐significant trend for lower hospitalizations due to psychosis in the Horyzons group vs. TAU (13% vs. 27%; OR=0.36, 95% CI: 0.11‐1.08, p=0.07, NNT=7). So, although we did not find a significant effect of Horyzons on social functioning compared with TAU, the intervention was effective in improving vocational or educational attainment, a core component of social recovery, and in reducing usage of hospital emergency services, a key aim of specialized first‐episode psychosis services. Horyzons holds significant promise as an engaging and sustainable intervention to provide effective vocational and relapse prevention support for young people with first‐episode psychosis beyond specialist services.